PERTUMBUHAN DAN REPRODUKSI IKAN LAYANG BIRU (Decapterus macarellus) DI PERAIRAN MALUKU UTARA [Growth and reproduction of mackerel scads, Decapterus macarellus (Cuvier, 1833) in North Moluccas waters] - Kusdi Hi. Iksan; Irham Irham (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2009)
The study about growth and reproduction of mackerel scads in North Moluccas was conducted from January to May 2008 using purse seine. Total samples are 2000 fishes comprise 645 males and 1355 females. The growth of female fish faster than male and both of this fish reached maximum length at age 4 years. Negative allometric growth patterns were found both in female and male. All fish samples dominated by immature fish. The most mature fish was found in March and the first maturity fish reached at 258 mm of total length. The peak of spawning season was found in April-May and fecundity was ranged from 28,875 to 84,000 eggs. The number of eggs has a positive correlation with total length.